ANALISIS FINANSIAL USAHA PETERNAKAN AYAM PEDAGING DENGAN POLA KEMITRAAN - Suwianggadana, I P. A.; ,, Suciani; Sarini, N. P. (Jurnal Peternakan Tropika, 2014)
This study was conducted in April 2012 using secondary data that is the result of the project the Australian Center for International Agricultural Research (ACIAR) AH 169/2006 on the cheap and effective biosecurity for broiler farmers sector 3 in Indonesia, meaning that the people who carry out farm biosecurity is limited. This study aims to calculate how much income and the value of R / C ratio in broiler farmers in Selan Bawak Village, District Marga, Tabanan regency. The number of farmers involved as many as 20 people each is a partnership of PT. A 11 people and PT. B 9 people. Data were analyzed by using methods of Financial Analysis. The results showed that the average total cost for broiler livestock business partnership is Rp 89,932,378 (A) and Rp92.854.805 (B), the BEP units = 1.379 tail (A), 1,380 individuals (B). Total revenue for the (A) Rp96.068.455 and (B) Rp 99,881,523. When the price per kg of live chickens in the contract is Rp 13.486 (A) and Rp 13 167 (B) then the revenue obtained is Rp 6,136,076 farmers partners A and B are Rp7.026.718. Based on the analysis of broiler livestock business with the partnership in the period March 10 to April 15 in 2012 showed a farmers partnership benefits A and B. Is evident from the results of the R / C ratio for plasma farmers A and B show the value of> 1 that is equal to 1.07 and 1.08. It means that the broiler livestock business with a decent partnership to be developed.
Keywords: enterprises financial analysis, income, pattern partnerships